Microdevice arrays with strain sensors for 3D mechanical stimulation and monitoring of engineered tissues. (July 2018) - Liu, Haijiao; MacQueen, Luke A.; Usprech, Jenna F.; Maleki, Hoda; Sider, Krista L.; Doyle, Matthew G.; Sun, Yu; Simmons, Craig A.
Abstract: Native and engineered tissue development are regulated by the integrative effects of multiple microenvironmental stimuli. Microfabricated bioreactor array platforms can efficiently dissect cue-response networks, and have recently integrated critical 2D and 3D mechanical stimulation for greater physiological relevance. However, a limitation of these approaches is that assessment of tissue functional properties is typically limited to end-point analyses. Here we report a new deformable membrane platform with integrated strain sensors that enables mechanical stretching or compression of 3D cell-hydrogel arrays and simultaneous measurement of hydrogel construct stiffness in situ. We tested the ability of the integrated strain sensors to measure the evolution of the stiffness of cell-hydrogel constructs for two cases. First, we demonstrated in situ stiffness monitoring of degradable poly (ethylene glycol)-norbornene (PEG-NB) hydrogels embedded with mesenchymal stromal cells (MSCs) and cultured with or without cyclic tensile stimulation for up to 15 days. Whereas statically-cultured hydrogels degraded and softened throughout the culture period, mechanically-stimulated gels initially softened and then recovered their stiffness corresponding to extensive cell network and collagen production. Second, we demonstrated in situ measurement of compressive stiffening of MSC-seeded PEG-NB gels cultured statically under osteogenic conditions, corresponding to increased mineralization and cellularization. This measurement technique can be generalized to other relevant bioreactor and organ-on-a-chip platforms to facilitate online, non-invasive, and high-throughput functional analysis, and to provide insights into the dynamics of engineered tissue development that are otherwise not available.